Blood Pressure, Stress Level, and Age with Sleep Quality in Elderly - Hatmanti, Nety Mawarda; Septianingrum, Yurike; Martining Wardani, Erika; Rusdianingseh; Sa’diyah, Alimatus (Universitas Nahdlatul Ulama Surabaya, 2024)
The ageing process in the elderly will cause several changes in the life cycle, one of which is in terms of sleep needs. Elderly sleep needs include sleep quality and quantity. The causes of both disorders are not only due to ageing factors but can also be caused by physical illness and psychological conditions of the elderly. Analyzing the relationship of blood pressure, stress level and age with sleep quality in the elderly. Using descriptive analytics with cross sectional methods. The population was 46 elderly, with simple random sampling technique obtained a sample of 42 elderly. Independent variables are blood pressure, stress level and age. The dependent variable is sleep quality. Blood pressure was associated with sleep quality (ρ =0.003), stress level was associated with sleep quality (ρ =0.008) and there was no association between age and sleep quality (ρ =0.936). The elderly need attention and support from people around them to carry out management in controlling blood pressure, stress levels and fulfillment of daily needs.